Contributi per una flora vascolare di Toscana. XVI (1055-1158) - Peruzzi, Lorenzo; Viciani, Daniele; Aldi, Marina; Angiolini, Claudia; Bajona, Enrico; Bonari, Gianmaria; Campo, Margherita; Cannucci, Silvia; Ceschin, Simona; Cianchi, Fabio; De Simone, Leopoldo; Fanfarillo, Emanuele; et al. (2024)
New localities and/or confirmations concerning 104 specific and subspecific plant taxa of Tuscan vascular flora, belonging to 95 genera and 45 families are presented: Baldellia (Alismataceae), Amaranthus (Amaranthaceae), Allium, Ipheion (Amaryllidaceae), Aethusa, Ferula, Magydaris, Trochiscanthes (Apiaceae), Vinca (Apocynaceae), Lemna (Araceae), Aristolochia (Aristolochiaceae), Hyacinthoides, Nectaroscilla, Prospero (Asparagaceae), Asplenium (Aspleniaceae), Ambrosia, Antennaria, Artemisia, Cirsium, Gamochaeta, Gnaphalium, Helianthus, Matricaria, Onopordum, Senecio, Tanacetum, Tolpis (Asteraceae), Berberis (Berberidaceae), Myosotis (Boraginaceae), Eruca, Isatis, Lepidium, Mummenhoffia, Turritis (Brassicaceae), Stellaria (Caryophyllaceae), Convolvulus (Convolvulaceae), Sedum (Crassulaceae), Hesperocyparis (Cupressaceae), Carex, Schoenoplectus (Cyperaceae), Chrozophora, Euphorbia (Euphorbiaceae), Astragalus, Coronilla, Lathyrus, Lotus, Onobrychis, Securigera, Trifolium, Vicia, Wisteria (Fabaceae), Najas (Hydrocharitaceae), Chamaeiris, Moraea (Iridaceae), Luzula (Juncaceae), Satureja, Stachys, Teucrium (Lamiaceae), Utricularia (Lentibulariaceae), Tulipa (Liliaceae), Alcea (Malvaceae), Ludwigia (Onagraceae), Ophrys (Orchidaceae), Phelipanche (Orobanchaceae), Corydalis, Hypecoum (Papaveraceae), Chrysopogon, Echinochloa, Eleusine, Gastridium, Hordeum, Lagurus, Nassella, Parapholis, Trisetaria (Poaceae), Persicaria (Polygonaceae), Groenlandia, Potamogeton (Potamogetonaceae), Aquilegia, Delphinium, Hepatica, Ranunculus (Ranunculaceae), Mespilus, Rosa, Rubus (Rosaceae), Galium (Rubiaceae), Ruta (Rutaceae), Azolla (Salviniaceae), Saxifraga (Saxifragaceae), Buddleja, Verbascum (Scrophulariaceae), Datura (Solanaceae), Phyla (Verbenaceae), Viburnum (Viburnaceae), Parthenocissus (Vitaceae). In the end, the conservation status of the units and eventual protection of the cited biotopes are discussed.